2011
DOI: 10.2478/v10078-011-0063-4
|View full text |Cite
|
Sign up to set email alerts
|

Somatotype is More Interactive with Strength than Fat Mass and Physical Activity in Peripubertal Children

Abstract: The purpose of this study was to analyse the interaction between somatotype, body fat and physical activity in prepubescent children. This was a cross-sectional study design involving 312 children (160 girls, 152 boys) aged between 10 and 11.5 years old (10.8 ± 0.4 years old). Evaluation of body composition was done determining body mass index and body fat by means of skin-fold measurements, using the method described by Slaughter. Somatotype was computed according to the Carter’s method. Physical activity was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
15
0
3
Order By: Relevance
“…In addition to the factors already elucidated regarding increasing the capacity to generate force, based on the literature, it can be speculated that body weight can reflect this relationship. Marta et al 24 found an association between body weight and the ESUL test reporting that obese children and adolescents performed better in the test, followed by the overweight. Furthermore, Casajús et al 25 also found that obese and overweight children and adolescents had better static strength test results (handgrip) when compared to normal weight children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the factors already elucidated regarding increasing the capacity to generate force, based on the literature, it can be speculated that body weight can reflect this relationship. Marta et al 24 found an association between body weight and the ESUL test reporting that obese children and adolescents performed better in the test, followed by the overweight. Furthermore, Casajús et al 25 also found that obese and overweight children and adolescents had better static strength test results (handgrip) when compared to normal weight children and adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…The somatotype has been defined as the quantification of the shape and composition of the human body, according to the measurements of anthropometry, it has been expressed in a three-number rating representing endomorphy (fatness), mesomorphy (musculature), and ectomorphy (linearity), (11). There are some studies indicating the association between the type of somatotypes and health conditions (12,13) as well as physical performance (14,15). While no study has been done to investigate the somatotype effect on dynamic balance control, a few studies have investigated its effects on the static balance control (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Neste período ocorrem mudanças relevantes no tamanho, forma e composição corporal da criança (Rogol, Clark, & Roemmich, 2000). Por sua vez, estas alterações têm impacto direto na prestação motora, com especial ênfase no desempenho das habilidades motoras fundamentais (Marta, Marinho, Costa, Barbosa, & Marques, 2011;Van den Tillaar & Ettema, 2004). Por exemplo, o incremento na estatura, associado a um maior comprimento das alavancas, tende a proporcionar um melhor desempenho em tarefas relacionadas com a projeção da bola (Van den Tillaar & Ettema, 2004).…”
Section: Introductionunclassified
“…A este respeito, foram reportadas correlações significativas e positivas das componentes endomórfica e mesomórfica com tarefas de projeção da bola em rapazes e raparigas pré-pubertárias. Pelo contrário, a componente ectomórfica evidenciou uma correlação inversa com o desempenho nessas tarefas (Marta et al, 2011).…”
Section: Introductionunclassified
See 1 more Smart Citation